ANTITESIS HERO’S JOURNEY DALAM NOVEL SENOPATI AWANG LONG KARYA HERMAN SALAM - Sulistyo, Kiftiawati; Mappatang, Nasrullah (JURNAL MELAYU SEDUNIA, 2019)
This study examines Herman Salam’s Senopati Awang Long Novel. This study focuses on Awang Long’s character as a General in Kutai Kertanegara Kingdom, Eastern of Kalimantan, Indonesia. The theory and approach used to analyze in this study are Hero’s Journey by Joseph Campbell. The method of this study is the qualitative research method. The data collection of this research uses literary research and interview. The result of this research concludes that Senopati Awang Long’s novel is an antithesis towards Hero’s Journey theory by Joseph Campbell. There are significant differences between the East Hero (Malay) and the West Hero.